Energy Efficient Data Intensive Distributed Computing - Xiong, Weiwei; Kansal, Aman (IEEE Data Engineering (Special Issue on Energy Aware Big Data Processing), 2011)
Many practically important problems involve processing very large data sets, such as for web scale data mining and indexing. An efficient method to manage such problems is to use data intensive distributed programming paradigms such as MapReduce and Dryad, that allow programmers to easily parallelize the processing of large data sets where parallelism arises naturally by operating on different parts of the data. Such data intensive computing infrastructures are now deployed at scales where the resource costs, especially the energy costs of operating these infrastructures, have become a significant concern. Many opportunities exist for optimizing the energy costs for data intensive computing and this paper addresses one of them. We dynamically right size the resource allocations to the parallelized tasks such that the effective hardware configuration matches the requirements of each task. This allows our system to amortize the idle power usage of the servers across a larger amount of workload, increasing energy efficiency as well as throughput. This paper describes why such dynamic resource allocation is useful and presents the key techniques used in our solution.